Sistem Informasi Kepegawaian Sekolah Dasar Negeri Di Kecamatan Sukodono Berbasis Web - Nurhasanah, Dewi; , Hernawan Sulistiyanto, S.T.,M.T (2016)
Personnel information system on an institution often still manual. State elementaryschools in District Sukodono are schools that require an information system to facilitate the processing of personnel data. Data processing at state elementary schools in District Sukodono still done manually or using Microsoft Word, especially on the staffing process of all personnel data. Data processing activities are activities that personnel spend enough time for the administration, but this activity is very important to know the identity of the personnel. Conventionally data processing does not have a database as a data storage. Therefore thesis entitled Web-Based Information Systems Public Elementary Schools in the District Sukodono is designed to produce an information system of accurate personnel data, and more easily applied for online-based information system already. The personnel information system is a medium that deal with processing and storage of personnel data created by using engineering software with waterfall method, and implemented using XAMPP with the programming language PHP, while for the MySQL database.